Electrochemical determination of Adrenaline and Uric acid at 2-Hydroxybenzimidazole modified carbon paste electrode Sensor: A voltammetric study - H.D. Madhuchandra; B.E. Kumara Swamy (Materials Science for Energy Technologies, 2020)
Herein 2-Hydroxybenzimidazole Modified Carbon Paste Electrode [MCPE] Sensor was developed by mechanochemical method for the electrochemical determination of Adrenaline (AD) and Uric acid (UA) by the cyclic voltammetric technique. The effects of pH, scan rate and concentration on the oxidation of Adrenaline and Uric acid were studied. The 2-Hydroxybenzimidazole [MCPE] was applied for the simultaneous determination of Adrenaline and Uric acid. The developed MCPE has capable of determining both AD and UA individually with two identical different oxidation peaks. The developed method is more sensitive and selective and the corresponding LOD 3.0 µM, LOQ 12.0 µM for AD and LOD 5.1 µM, LOQ 17.8 µM for UA respectively.